Sistem Informasi Geografis Obyek Wisata di Kabupaten Kudus - Setiaji, Pratomo (Universitas Muria Kudus, 2011)
The tourism service have been manually conducted in Kudus, in a such way they are served by books,brochure, poster,etc. for the every kind of tourists objects there.Tourism object mapping is an information which accurately presented dealing with the existence of the tourism object of a district and hardly needed in guiding the tourists. Moreover, it could be a media to promote the tourism destinations in Kudus. The information is presented in a particular ways called Geographic Information System (GIS) which data information related to a geographical condition of an area. Tourism object mapping is an information which accurately presented dealing with the existence of the tourism object of a district and hardly needed in guiding the tourists. Moreover, it could be a media to promote the tourism destinations in Kudus. The information is presented in a particular ways called Geographic Information System.GIS is addresed to emerge a system in which leads to find the coordinate of the tourist object in Kudus including the facility. The system is designed which UML modelled and utilized Quatum GIS dan Map Server then yield GIS to find the tourims coordinate.